Pregnant enemy, Christmas bride - Yates, Maisey (Harlequin presents, 2024)
It’s cold outside… but they’re playing with fire! CEO Florence Clare’s relationship with Hades Achelleos is…complicated. By day, her corporate enemy is the devil himself, their rivalry a thing of headline-grabbing legend. By night, they indulge in a clandestine affair. Equally brilliant, equally headstrong, they are one another’s forbidden rebellion… Hades is fire personified, and Florence has always known their entanglement becoming public would be disastrous. But this Christmas, two little lines threaten to reveal her darkest secret—she’s pregnant. And the paparazzi sense scandal when the Greek tycoon announces his shocking new bride-to-be…